I.Q., it's time - Fraser, Mary Ann. (New York : Walker ; [S.l.] : Distributed to the trade by Holztbrinck Publishers, 2005)
I.Q., a pet mouse, learns to tell time along with the rest of Mrs. Furber's class and worries about whether he will have his special project ready in time for Parents' Night.
2.8
K-3
Keywords: Mice -- Fiction; Time -- Fiction; Clocks and watches -- Fiction; Pets -- Fiction; Schools -- Fiction; Mice -- Fiction; Time -- Fiction; Clocks and watches -- Fiction; Pets -- Fiction; School stories